WHY THE ELECTRON IS NEGATIVELY CHARGED AND THE PROTON POSITIVELY? - Saleh, Gh; Alizadeh, Reza; Dalili, Asghar (MATTER: International Journal of Science and Technology, 2020)
Electron, proton and neutron are the most important Subatomic particles which made atoms. Between them neutron does not have any electric charge but electron is negative and against that proton is positive. We know the electron as an elementary particle and proton consists of two different kinds of elementary particles (up and down quarks). But we do not know structure of electron and proton. Saleh Theory defines a structure for electron as hollow sphere and for proton as continues texture. Here we proved that the electron and proton properties are due to its structure. So electrons moves easily and protons are like black hole because of their structure. This indicates that there is a possibility of obtaining best shape for electron and proton from Saleh Theory and it is possible to determine a structure for neutrons too which could help us to have better understand about particle physics examination.